A new species of the genus Claassenia (Plecoptera: Perlidae) from China - Xiang, Ya-Nan; Huo, Qing-Bo; Du, Yu-Zhou (Zootaxa, 2022)
A new species, Claassenia qingzanga Xiang, Huo & Du, sp. nov. is described from Tibet and Qinghai Province of western China, this is the first record of Claassenia in Qinghai-Tibet Plateau. Males of the new species are brachypterous, the apex of the aedeagus with tiny spines dorsally and with dense protrusion laterally. The new species is compared to all regional Claassenia.